2008
DOI: 10.1111/j.2151-6952.2008.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Visitor Meaning‐Making at Grand Canyon's Tusayan Museum and Ruin

Abstract: Meaning‐making describes a process by which visitors transform museum experiences into new knowledge and memories. Meaning‐making is influenced by visitors' leisure motivations, prior knowledge, socio‐cultural context brought to the experience, personally‐guided interpretation, and events since the visit. In this study, visitors' long‐term recollections included contextual references to how and why they remembered what they experienced. Forty visitors were interviewed by telephone six months after attending a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…People learn actively by negotiating meaning, and their background and prior experiences influence how and what they learn (Benton, 2008;Falk & Dierking, 1992;Hein, n.d., 1991Hein, n.d., , 1998Vygotsky, 1978). Von Glasersfeld (2005) elaborates that a scrutiny of meaning leads to individual experience and the social aspect of integrating the links between language and that experience.…”
Section: Constructivist Learning Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…People learn actively by negotiating meaning, and their background and prior experiences influence how and what they learn (Benton, 2008;Falk & Dierking, 1992;Hein, n.d., 1991Hein, n.d., , 1998Vygotsky, 1978). Von Glasersfeld (2005) elaborates that a scrutiny of meaning leads to individual experience and the social aspect of integrating the links between language and that experience.…”
Section: Constructivist Learning Theorymentioning
confidence: 99%
“…Topics such as reproduction, birth, death, competition and conflict, sickness, and social relationships are emotional areas for most humans" (p. 89). Therefore, the themes that are understood by and connect with the audience best are those that connect tangible artifacts with emotional universal concepts (Benton, 2008). Tilden's (1957) final principle of interpretation concentrates on interpretation for children.…”
Section: IVmentioning
confidence: 99%
See 1 more Smart Citation
“…Other how-to manuals on technique exist (e.g., Roth, 1998;Beck & Cable, 2002;Bridal, 2004), offering strategies and guidelines for practice that are based on vetted interpretive philosophy and learning theory. The small number of research studies that have been conducted suggest that making an emotional connection with the audience and linking interpretation with visitors' previous experiences and prior knowledge are hallmarks of effective interpretation (Gross & Zimmerman, 2002;Ballantyne, 2003;Benton, 2008).…”
Section: Costumed Interpreters' Beliefs and Practicesmentioning
confidence: 99%
“…This particular use of prior knowledge aligns with Tilden's first principle that "any interpretation that does not somehow relate what is being displayed or described to something within the personality or experience of the visitor will be sterile" (Tilden, 1957 as quoted in Gross & Zimmerman, 2002, p. 273). Research has shown the use of prior knowledge to connect with visitors is considered critical for successful interpretation (Gross & Zimmerman, 2002;Ballantyne, 2003;Benton, 2008).…”
Section: Prior Knowledge and Identity Influence Personal Connectionsmentioning
confidence: 99%